Distinct clinical, neuroimaging and genetic profiles of late-onset cobalamin C defects (cb1C): a report of 16 Chinese cases - Xianling Wang; Yanhui Yang; Xuying Li; Cunjiang Li; Chaodong Wang (Orphanet Journal of Rare Diseases, 2019)
Abstract Objective The importance of late-onset cobalamin C (cblC) disorder is underestimated in adults. Improved awareness on its clinical and neuroimaging features helps timely diagnosis and appropriate treatment. Methods Totally 16 late-onset cblC cases were diagnosed based on clinical, biochemical findings and MMAHC gene mutation analysis. Clinical presentations, neuroimaging features and mutational spectrum were reviewed. Results The case series included 10 males and 6 females, with average age of 22 (range 13–40) years. All the 16 patients displayed bilateral pyramidal tract signs, and most of the cases (13) had cognitive impairment. Other symptoms included psychiatric symptoms (6), epilepsy (6), peripheral nerve damage (5), ocular symptoms (4) and lower-limb thrombosis (1). The neuroimaging findings were dominated by cerebral atrophy (11/16), followed by white matter lesions (4), cerebellar lesions/atrophy (2) and spinal cord lesions (1). There were also 2 patients with normal imaging. All the MMACHC mutations were compound heterozygous, of which the most and second frequent was c.482G > A (p.R161Q; 15/16 case; allele frequency: 46.88%) and c.609G > A(p.W203X; 6/16 case; allele frequency: 18.75%). In addition, patients carrying frameshift mutations (deletion/duplication) presented more frequently with psychiatric symptoms (57.1%) and optic nerve damages (42.9%) than those carrying point mutations (22.2 and 11.1%, respectively). In contrast, peripheral nerve (44.4%) and white matter lesions (33.3%) were more frequently identified in point mutation- carriers. However, the differences did not achieve statistical significance (all p > 0.05). Conclusion Compared to the early-onset form, late-onset cblC displayed some clinical, neuroimaging and mutational profiles, which warrants particular attention in adult neurologic practice. These findings not only broaden our insights into the genotypes and phenotypes of the disease, but highlight the importance of early diagnosis and initiation of appropriate treatments.